Efficacy of high dose tranexamic acid (TXA) for hemorrhage: A systematic review and meta-analysis. Issue 3 (March 2023) - Hmidan Simsam, Mohammad; Delorme, Laurence; Grimm, Dylan; Priestap, Fran; Bohnert, Sara; Descoteaux, Marc; Hilsden, Rich; Laverty, Colin; Mickler, John; Parry, Neil; Rochwerg, Bram; Sherman, Christopher; et al.
Highlights: We conducted a systematic review and meta-analysis on studies that compared standard dose with high dose IV TXA, defined as ≥2 g or ≥30 mg/kg as a single bolus, in adults (≥ 16 years of age) with hemorrhage. When compared to standard dose, high dose IV TXA probably reduces transfusion requirements (OR, 0.86; 95% CI, 0.76–0.97; p  = 0.01) with an uncertain effect on thromboembolic events and mortality. Despite an uncertain effect on mortality, high dose TXA may be able to play an integral role in survival, particularly when the risk of exsanguination is high. Abstract: Background: Standard dose (≤ 1 g) tranexamic acid (TXA) has established mortality benefit in trauma patients. The role of high dose IV TXA (≥2 g or ≥30 mg/kg as a single bolus) has been evaluated in the surgical setting, however, it has not been studied in trauma. We reviewed the available evidence of high dose IV TXA in any setting with the goal of informing its use in the adult trauma population. Methods: We searched MEDLINE, EMBASE and unpublished sources from inception until July 27, 2022 for studies that compared standard dose with high dose IV TXA in adults (≥ 16 years of age) with hemorrhage. Screening and data abstraction was done independently and in duplicate. We pooled trial data using a random effects model and considered randomized controlled trials (RCTs) and observational cohort studies separately. We assessed the individual study risk of bias using the Cochrane Risk of Bias for RCTs and the Newcastle-Ottawa Scale for observational cohort studies. The overall certainty of evidence was assessed using the GRADE approach (Grading of Recommendations Assessment, Development and Evaluation). Results: We included 20 studies with a combined total of 12, 523 patients. Based on pooled RCT data, and as compared to standard dose TXA, high dose IV TXA probably decreases transfusion requirements (odds ratio [OR] 0.86, 95% confidence interval [CI] 0.76 to 0.97, moderate certainty) but with possibly no effect on blood loss (mean difference [MD] 43.31 ml less, 95% CI 135.53 to 48.90 ml less, low certainty), and an uncertain effect on thromboembolic events (OR 1.33, 95% CI 0.86 to 2.04, very low certainty) and mortality (OR 0.70, 95% CI 0.37 to 1.32, very low certainty). Conclusion: When compared to standard dose, high dose IV TXA probably reduces transfusion requirements with an uncertain effect on thromboembolic events and mortality. Level of Evidence: Systematic review and meta-analysis, level IV.